Silence and the Voice in Anorexia Nervosa - Domenico Cosenza (EJP import test, 2015)
Summary: The focus of this article is the function of Speech and Silence in the clinic of Anorexia Nervosa. A Lacanian approach in this field can provide an important contribution to this particular aspect of clinical experience with anorexia. My thesis is that there is a defect of metaphorisation in the use of the function of Speech and Silence in the experience of the subject in anorexia. This thesis finds support in the relationship of anorexic patients with their words and silences as evidenced in both clinical interviews and psychotherapy. This relationship reveals a non-dialectical way of locating oneself in the dimension of language, and a holophrastic rather than metaphorical linguistic practice. A Lacanian approach allows us to both isolate this structural knot in the heart of anorexia nervosa and distinguish anorexia nervosa from hysterical-neurotic forms of anorexia.
Keywords: anorexia; Holophrasis; Silence; Super-ego; voice